Specialization Versus Diversification as Alternative Strategies for Sustainable Growth in Resource-rich Developing Countries. Case of Nigeria - Young, Ademola Obafemi (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2022)
The question of whether developing countries should pursue specialization or diversification in export as a driver of sustainable economic growth has been a subject of an intense debate in economic literature. At present, one understanding of the debate, as postulated by Imbs and Wacziarg (2003), is that economies grow through two stages of diversification and concentration as income grows: they initially diversify but re-specialize once a (relatively) high level of income per capita is attained. A U-shaped curve best explains the notion. With Nigeria as a reference country, we employed ARDL procedure and examined the aforementioned exposition over the period 1960-2019. Specifically, the non-monotonic relationship between diversification and growth is examined. In furtherance, we examined the impact of diversification on the effect of non-oil exports on growth. Employing an augmented production-function framework and two distinct measures of diversification, we find, contrary to the Imbs-Wacziarg notion, a monotonic (increasing) relationship between diversification and growth, suggesting that diversification, rather than specialization, continues with growth. Applying a similar framework and five different measures of non-oil exports, we find that the impact of diversification on the effects of agricultural and industrial sectors on growth is higher, as compared to building and construction, wholesale and retail, services sectors.